Suction cup denture for restoration of maxillary edentulousness with hemilateral maxillary defects: a case report - Lin, Kaijie; Wang, Yanhui; Wang, Jianxin; Ma, Lei (Frontiers in Dental Medicine, 2025)
This single case report describes the rehabilitation of a 71-year-old man with a hemimaxillary defect following resection of maxillary gingival carcinoma and reconstruction with a pedicled submental island flap. Conventional prosthetic rehabilitation had failed to provide adequate retention, and implant therapy was contraindicated due to prior radiotherapy. A suction cup denture was fabricated as a minimally invasive alternative to restore function. At six months, the denture demonstrated satisfactory retention, stability, and masticatory efficiency, with the patient reporting improved comfort, speech, and quality of life, and no persistent mucosal complications were observed. This case suggests that suction cup dentures may serve as a temporary, low-cost, and functionally effective option for hemimaxillectomy patients with specific indications, provided that wearing time is restricted and close follow-up is maintained to minimize risks.